Validation of The Gravimetry Method for Determining Rare Earth Elements Oxides - Pratama, Afiq Azfar; Hidayat, Amalia Ekaputri; Rommy, Rommy; Indryati, Suci; Laksmana, Roza Indra; Trinopiawan, Kurnia; Purwanti, Tri; Widana, Kurnia Setiawan; Putra, Aditya Widian; Anggraini, Mutia; Nasrullah, Dzaki Hasan (Badan Riset dan Inovasi Nasional, 2024)
The demand for minerals to meet technological developments is increasing, including minerals that contain rare earth elements (REE). The levels of REE in solids can be determined using conventional analysis methods (gravimetry) and instruments. Even though the instrument method provides more accurate results with a small amount of analyte, the cost is higher compared to the gravimetric method, which requires more analyte and provides good results. Therefore, the gravimetric method is a solution for areas with limited instruments and budgets. The study aims to validate the gravimetric method for determining REE oxides levels, evaluate its precision and accuracy, and assess its feasibility of use. In this study, two methods were used for REE analysis: the ASTM E2941-14 method with sample weight modification and the addition of acid to increase REE oxides recovery and a precipitation method using oxalic acid. The validation stages include sample dissolution, precipitation, filtration, and ash-making. The research results show that the RSD value is 0.3154, which is smaller than 2/3 of Horwitz's CV, namely 4.1727, which means it meets the precision acceptance requirements of ISO/IEC 17025:2017. The REE oxides recovery value, which indicates accuracy, also increased to 97.74%. Therefore, the gravimetric method can be used as an alternative for determining REE oxides levels.